The things we keep – an ethnographic study of material possessions in New York City. (18th November 2020) - Bennett, Sam
Abstract : A home could be likened to a glimpse into our heads. The plaster and lath are the skin and bones, our skull of sorts, a container of all things, sitting, waiting to be observed. The things we keep silently, but visually tell a story of us. Is this why we keep them? So as not to erase our identity? This essay sets out to understand consumer culture through people's most special things in their domestic spaces. With an ethnographic approach, influenced by The Meaning of Things, I conducted in-person interviews, surveys, and workshops with residents discussing their most special things. From these findings, I created Home Moves prompts to re-engage with our things, and a speculative Living Room Lobby to transform personal collections outside of the domestic space.